2010
DOI: 10.1016/j.neuron.2009.12.003
|View full text |Cite
|
Sign up to set email alerts
|

5-HT1A Autoreceptor Levels Determine Vulnerability to Stress and Response to Antidepressants

Abstract: Summary Most depressed patients don't respond to their first drug treatment, and the reasons for this treatment resistance remain enigmatic. Human studies implicate a polymorphism in the promoter of the serotonin-1A (5-HT1A) receptor gene in increased susceptibility to depression and decreased treatment response. Here we develop a new strategy to manipulate 5-HT1A autoreceptors in raphe nuclei without affecting 5-HT1A heteroreceptors, generating mice with higher (1A-High) or lower (1A-Low) autoreceptor levels.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
403
1
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 395 publications
(436 citation statements)
references
References 63 publications
24
403
1
8
Order By: Relevance
“…Our results also agree with those found recently using conditional knockout mice for presynaptic 5-HT 1A R. 43 Both studies indicate that the selective -yet partialreduction of 5-HT 1A -autoreceptor expression with unchanged postsynaptic 5-HT 1A R expression evokes antidepressant-like behavior and augments SSRI effects.…”
Section: Discussionsupporting
confidence: 93%
“…Our results also agree with those found recently using conditional knockout mice for presynaptic 5-HT 1A R. 43 Both studies indicate that the selective -yet partialreduction of 5-HT 1A -autoreceptor expression with unchanged postsynaptic 5-HT 1A R expression evokes antidepressant-like behavior and augments SSRI effects.…”
Section: Discussionsupporting
confidence: 93%
“…Our results show that decreases in 5-HT1A autoreceptors during development impact anxiety-related behaviors but not depression-related behaviors. In contrast, decreases in 5-HT1A autoreceptors in adulthood have no effect on anxiety-related behavior and result in lower levels of depression-related behaviors (Bortolozzi et al, 2012;Richardson-Jones et al, 2010). Thus, the temporal-and region-specific aspects of receptor variability, as impacted by either genetic or epigenetic factors, may have dissociable effects on psychiatric disease risk at different points of the life course, adding a layer of complexity to our understanding of psychiatric risk alleles.…”
Section: -Ht1a-mediated Anxiety Phenotypes Are Developmental In Originmentioning
confidence: 99%
“…Manipulation of 5-HT1A receptors at different time points has revealed a dissociable role for autoreceptor versus heteroreceptor populations during development and adulthood Richardson-Jones et al, 2011). In particular, whole life, but not adult-specific, suppression of autoreceptors leads to increased anxiety, a finding recently confirmed via RNAi knockdown of autoreceptors in adulthood (Bortolozzi et al, 2012;Richardson-Jones et al, 2010). In contrast, developmental suppression of forebrain heteroreceptors does not affect anxiety levels but appears to be important for modulating stress reactivity and depression-related behaviors (Richardson-Jones et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…One of the widely discussed causes is a polymorphism of 5-HT1A receptor-encoding gene, Htr1a [32,33]. A mechanism by which SSRI exert their antidepressant effects involves the desensitization of presynaptic 5-HT1A receptors due to the rise of the extracellular 5-HT [34][35][36][37].…”
Section: Fluoxetine Monotherapymentioning
confidence: 99%
“…A mechanism by which SSRI exert their antidepressant effects involves the desensitization of presynaptic 5-HT1A receptors due to the rise of the extracellular 5-HT [34][35][36][37]. It has been suggested that the ability of SSRI to desensitize presynaptic 5-HT1A receptors requires certain maximal level of their expression, and that individuals with the Htr1a C(-1019)G polymorphism (referred to as G/G allele carriers), are resistant to SSRI due to the previously described normal levels of these receptors [32,38]. At the same time, several studies failed to prove the association between this genetic trait and failure of SSRI to improve depression [39].…”
Section: Fluoxetine Monotherapymentioning
confidence: 99%